Validation of the Korean version of the Summated Xerostomia Inventory among older adults residing in nursing homes - SeolHwa Moon; Eunmi Oh; Daum Chung; Rina Choi; Gwi-Ryung Son Hong (BMC, 2024)
Abstract Background Xerostomia is commonly experienced by older individuals. We sought to develop and evaluate the reliability and validity of the Korean version of the Summated Xerostomia Inventory (K-SXI) among older adults residing in long-term care facilities (LTCFs) in Korea. Methods In this secondary data analysis study using cross-sectional data, a cross-cultural adaptation process was conducted for the Korean version before data collection. Data collection was conducted from July 2021 to January 2022, targeting 544 older adults in 16 LTCFs. Data analysis included intraclass correlation coefficient (ICC) for test-retest reliability, and Cronbach's α for internal consistency reliability. Exploratory and confirmatory factor analyses were used to verify construct and convergent validity. Test-retest analysis was performed 6 weeks after baseline. Convergent and concurrent validities were assessed with age group and the xerostomia standard single question, respectively. Results A total of 544 older adults participated in this study. The mean of total K-SXI score was 11.70 (standard deviation, 4.96) points. The ICC value was calculated to be 0.90, and Cronbach's α of K-SXI was 0.92. Exploratory factor analysis revealed a single factor, explaining 74.8% of the total variance, however, some goodness-of-fit indices of the single factor model were found to be unsuitable in confirmatory factor analysis. The convergent and concurrent validity were supported. Conclusion The present study provides evidence supporting the validity and reliability of the K-SXI for measuring xerostomia in institutionalized older adults in Korea.